2006
DOI: 10.1073/pnas.0603693103
|View full text |Cite
|
Sign up to set email alerts
|

A mitotically inheritable unit containing a MAP kinase module

Abstract: Prions are novel kinds of hereditary units, relying solely on proteins, that are infectious and inherited in a non-Mendelian fashion. To date, they are either based on autocatalytic modification of a 3D conformation or on autocatalytic cleavage. Here, we provide further evidence that in the filamentous fungus Podospora anserina, a MAP kinase cascade is probably able to self-activate and generate C, a hereditary unit that bears many similarities to prions and triggers cell degeneration. We show that in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
110
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(116 citation statements)
references
References 16 publications
4
110
2
Order By: Relevance
“…However, unlike classical prions based on alternate conformations of proteins, the C hereditary unit seems to rely on the "ON" state of the PaMpk1 cascade. As described for the JNK cascade of Xenopus oocytes (Bagowski and Ferrell 2001), the PaMpk1 cascade would present a positive regulatory loop whereby a component downstream of the cascade upregulates an upstream component in trans (Kicka et al 2006). Therefore, once one molecule of the pathway is activated, the activation could spread to the other nonactive molecules and lock them in the ON state.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, unlike classical prions based on alternate conformations of proteins, the C hereditary unit seems to rely on the "ON" state of the PaMpk1 cascade. As described for the JNK cascade of Xenopus oocytes (Bagowski and Ferrell 2001), the PaMpk1 cascade would present a positive regulatory loop whereby a component downstream of the cascade upregulates an upstream component in trans (Kicka et al 2006). Therefore, once one molecule of the pathway is activated, the activation could spread to the other nonactive molecules and lock them in the ON state.…”
mentioning
confidence: 99%
“…Involvement of the PaMpk1 MAPK pathway was discovered through a traditional genetics approach, i.e., we identified mutants unable to develop CG (IDC mutants with Impaired Development of CG) and found that two of the mutated genes encode the MAPKKK and MAPKK of the cascade (Kicka and Silar 2004;Kicka et al 2006). Reverse genetics showed that the PaMpk1 MAPK gene also controls CG (Kicka et al 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations